A MOC-based neutron kinetics model for noise analysis. (March 2020) - Gammicchia, A.; Santandrea, S.; Zmijarevic, I.; Sanchez, R.; Stankovski, Z.; Dulla, S.; Mosca, P.
Highlights: A new kinetic model for noise analysis is proposed. A new concept of dynamic eigenvalue adapted to noise phenomena is introduced. Higher order quadrature formulas to compute fission-delayed integrals are used. Abstract: A 2-D noise model is implemented in the deterministic reactor code APOLLO3® to simulate a periodic oscillation of a structural component. The Two/Three Dimensional Transport (TDT) solver, using the Method of Characteristics, is adopted for the calculation of the case studies, constituted by a moving detector and control-rod bundle. The periodic movement is built by properly linking the geometries corresponding to the temporal positions. The calculation is entirely performed in the real time domain, without resorting to the traditional frequency approach. A specifically defined dynamic eigenvalue is used to renormalize in average the reactivity over a period. The algorithm is accelerated by the DP N synthetic method. For each cell of the domain, the time values of fission rates are analysed to determine the noise extent. Moreover we propose a systematic approach to the definition of the macroscopic cross sections to be used in dynamical calculations starting from library data. As an aside of our work we have found that even in static calculation this approach can produce significant changes.